STUDY REGARDING THE IMPORTANCE OF MONITORING PHYSIOLOGICAL PARAMETERS IN ELITE FENCING - TĂTĂRAN, Amalia; TEODORESCU, Silvia; BALTAG, Oana Maria; APOSTU, Mihaela (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2023)
Introduction. Fencing is a sport that requires psychomotor skills, explosive power, movement speed, reaction speed and physical endurance. Epée and foil fencers have higher aerobic capacity than sabre fencers, whereas épée and foil fencers have similar aerobic capacity. In fact, this can be due to more aerobic nature of épée and foil weapons compared with sabre. Measurement of maximum oxygen uptake (VO2max) is the standard index of cardiorespiratory fitness, but is practical only in a laboratory setting. Over time, numerous VO2 tests have shown that VO2max is a quantifiable and reproducible parameter of the cardiorespiratory system’s ability to meet maximum oxygen requirements. Objective. The aim of this study is to show the importance of monitoring physiological parameters by the Bruce protocol in elite fencing, specifically women’s épée, in order to manage the physical training plan. Methodology. Cardiopulmonary fitness is monitored in dynamic conditions by testing VO2max with the Bruce protocol of the COSMED treadmill Ergometer. This study was carried out over period of 8 weeks in 2021. It should be mentioned that these tests were performed after a specific training plan adapted to the pandemic period. Were included 4 female épée fencers, members of the Romanian National Fencing Team, aged between 22 and 36 years and with outstanding results at national and international levels. Results. From the total of tested physiological parameters were selected the protocol parameters (speed, treadmill incline, time) and metabolic parameters (absolute oxygens consumed (ml/min), maximum oxygens consumed (ml/min/kg), metabolic equivalents, respiratory coefficient, heart rate). These indicators were assessed for anaerobic threshold, respiratory compensation point and at the end of the test. The evolution of these parameters was followed between tests for each subject. Discussions and conclusions. The Bruce Protocol estimates maximal oxygen consumption (VO2 max) as a measure of the athlete’s aerobic capacity during sustained effort. In this context, the obtained results highlight an increase of the cardiorespiratory fittness to the women’s épée, an efficient distribution of the oxygen to the tissues and a better adaptation of the cardiac function to the effort. In conclusion, the cardiorespiratory capacity monitoring through the Bruce Protocol can be an important guideline for the physical training to the elite épée fencers. REZUMAT. Studiu privind importanța monitorizării parametrilor fiziologici în scrima de performanță. Introducere. Sportivii care practică spadă și floretă au o capacitate aerobă mai mare decât cei care practică sabie, întrucât scrimerii de spadă și floretă au o capacitate aerobă similară. Obiective. Scopul acestui studiu este de a demonstra importanța monitorizării în dinamică a parametrilor funcționali la sportivele lotului național de scrimă, mai precis spadă, în vederea dirijării planului de pregătire. Mijloace și metode. Capacitatea cardiorespiratorie a fost monitorizată în dinamică, prin aplicarea protocolului Bruce COSMED treadmill Ergometer. S-au evaluat 4 spadasine, cu vârste între 22 și 36 de ani, membre ale lotului național de scrimă și cu performanțe mondiale și olimpice, pe o perioadă de 8 săptămâni, în 2021. Trebuie menționat faptul că aceste testări s-au efectuat după un program de antrenament adaptat perioadei pandemice. Rezultate. Din totalul indicatorilor înregistrați prin protocolul Bruce s-au selectat parametrii de testare (viteza de alergare, gradul de înclinare al platformei, timpul) și parametrii metabolici (consumul absolut de oxigen (ml/min), VO2 maxim (ml/min/kg), frecvența cardiacă, echivalentul metabolic și coeficientul respirator). Acești indicatori au fost apreciați pentru pragul anaerob, punctul de compensare respiratorie și la finalul testului. Pentru fiecare subiect s-a urmărit evoluția acestor indicatori între testări. Discuții și concluzii. Testul Bruce estimează absorbția maximă de oxigen (VO2 max), ca măsură a capacității aerobe a atletului în efort susținut. Toate sportivele s-au adaptat rapid la planul de pregătire după „blocajul” pandemic, reușind în 8 săptămâni de pregătire fizică să-și îmbunătățească sau să-și mențină capacitatea cardiopulmonară la pragul „excelent” conform normelor de referință standard. În acest context, rezultatele obținute evidențiază și o distribuire eficientă a oxigenului la țesuturi corelată cu o bună adaptare a funcției cardiace la efort. În concluzie, monitorizarea funcției cardiorespiratorii prin protocolul Bruce poate reprezenta un important criteriu în dirijarea pregătirii fizice a spadasinelor din lotul național. Cuvinte cheie: capacitate cardiorespiratorie, protocol Bruce, scrima de performanță Received 2023 January 17; Revised 2023 March 22; Accepted 2023 March 23; Available online 2023 May 30; Available print 2023 June 30.